2021
DOI: 10.1021/acs.orglett.1c02730
|View full text |Cite
|
Sign up to set email alerts
|

Xylarins A–D, Two Pairs of Diastereoisomeric Isoindoline Alkaloids from the Endolichenic Fungus Xylaria sp.

Abstract: Two pairs of diastereoisomeric isoindoline alkaloids, xylarins A–D (1–4), were isolated from the endolichenic fungus Xylaria sp. Xylarins A and B (1 and 2) possess a previously undescribed 5/6/5–5/6 polycyclic scaffold, featuring a combination of a novel dihydrobenzofurone unit and an isoindoline unit, while xylarins C and D (3 and 4) contain an additional N,N-dimethylaniline at the C-3′ position. Their structures were elucidated by comprehensive spectroscopic analyses combined with single-crystal X-ray diffra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In 2021, Xu et al reported the isolation of two pairs of diastereoisomeric isoindoline alkaloids, xylarins A-D (348-351), from the endolichenic fungus Xylaria sp., which was obtained from the lichen of Parmelia sp. [81]. Among them, compounds 348 and 349 possess an unprecedented skeleton comprising a complex 5/6/5-5/6 polycyclic ring system and exist as a pair of diastereoisomers, while another pair of diastereoisomers, diastereoisomers 350 and 351, contain an additional N,N-dimethylaniline moiety at the C-3 ′ position.…”
Section: Alkaloids and Their Biological Activitiesmentioning
confidence: 99%
“…In 2021, Xu et al reported the isolation of two pairs of diastereoisomeric isoindoline alkaloids, xylarins A-D (348-351), from the endolichenic fungus Xylaria sp., which was obtained from the lichen of Parmelia sp. [81]. Among them, compounds 348 and 349 possess an unprecedented skeleton comprising a complex 5/6/5-5/6 polycyclic ring system and exist as a pair of diastereoisomers, while another pair of diastereoisomers, diastereoisomers 350 and 351, contain an additional N,N-dimethylaniline moiety at the C-3 ′ position.…”
Section: Alkaloids and Their Biological Activitiesmentioning
confidence: 99%
“…Xylariaceae is one of the largest, most commonly encountered, and highly diverse fungal families of the Ascomycota [4]. The genus Xylaria, belonging to the family Xylariaceae, is medicinal fungi commonly found in decaying plant tissues and is widely distributed in temperate, tropical, and subtropical regions [5,6]. So far, more than 200 bioactive compounds (>100 new ones) were isolated from Xylaria, including cytochalasins, α-pyrones, cyclopeptides, terpenoids, lactones, and succinic acid derivatives [7].…”
Section: Introductionmentioning
confidence: 99%
“…The isoindole skeleton is ubiquitous in a large variety of biologically active molecules and natural products, showing prominent biological and pharmaceutical activities . Over the past years, many efforts have been made to develop efficient methods for synthesizing isoindoles and isoindolines, including metal-catalyzed enantioselective C–H activation .…”
Section: Introductionmentioning
confidence: 99%